2015
DOI: 10.1515/bsrj-2015-0003
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Value at Risk Measurement on Emerging Stock Markets: Case of Montenegro

Abstract: Background: The concept of value at risk gives estimation of the maximum loss of financial position at a given time for a given probability. The motivation for this analysis lies in the desire to devote necessary attention to risks in Montenegro, and to approach to quantifying and managing risk more thoroughly. Objectives: This paper considers adequacy of the most recent approaches for quantifying market risk, especially of methods that are in the basis of extreme value theory, in Montenegrin emerging market b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Nocetti 55 extended the research made by Blejer and Schumacher 56 who suggested that Central Bank's Value at Risk (VaR) could be used as an early warning indicator of financial crises. 57 Research results showed that there is strong relationship among different measures focused on value at risk and several univariate leading indicators. Pazour 58 focused on two standard methods for development of the early warning system: (i) the signal approach and (ii) the regression probit or logit model approach.…”
Section: Early Warning Systems According To Type Of Crisismentioning
confidence: 96%
“…Nocetti 55 extended the research made by Blejer and Schumacher 56 who suggested that Central Bank's Value at Risk (VaR) could be used as an early warning indicator of financial crises. 57 Research results showed that there is strong relationship among different measures focused on value at risk and several univariate leading indicators. Pazour 58 focused on two standard methods for development of the early warning system: (i) the signal approach and (ii) the regression probit or logit model approach.…”
Section: Early Warning Systems According To Type Of Crisismentioning
confidence: 96%
“…Results of the empirical analysis on Montenegrin stock exchange show that the assessments of Value at Risk based on extreme value theory outperform econometric and quantile evaluations according to Cerovic [15] concluding that econometric evaluations prove to be on the lower bound possible Value at Risk movements.…”
Section: Literature Reviewmentioning
confidence: 98%
“…VaR has gained rapid acceptance as a valuable approach to address and measure market risk because of its ability to quantify risk in a single number. Authors, among others (Jadhav and Ramanathan [3]; Rodrigues [4]; Guhary [5]; Cerovic [6]; Vladimir [7] and Ringqvist [8]) have estimate risk using parametric methods and nonparametric methods, in parametric a specified distribution is fitted to the observed returns by calibrating the parameters. This method is, of course, very sensitive to the assumption of distribution.…”
Section: Introductionmentioning
confidence: 99%